نظریۂ حلول اسلام اور عیسائیت کے تناظر میں: کینتھ کریگ کے افکار کا جائزہ (Al-Qamar, 2023)
In Christisan theology, the doctrine of Incarnation holds that Jesus, the second hypostasis of the trinity, God the son and son of the father, taking on a human body and human nature was made flesh. Incarnation is a Christian faith which means that God incarnated in Jesus Christ.Christian say that word of God (Kalamatullah) made flesh and Jesus became Christ (Son of God). Kenneth cragg(A renowned Christian scholar on Islam.He wrote more than sixty books, most of them are on Islam)said that the concept of incarnation is also present in Islam, the revelation of the Holy Quran, Prophet-hood of Muhammadﷺ and the Muslims love for Muhammadﷺ is also like incarnation as in Christianity. In this article we discussed the concept of incarnation in Islam and Christianity and concluded that the revelation of theHoly Quran and the Prophet-hood of Muhammad ﷺis not an incarnated as Christian believe about Jesus.
Keywords: Religious theology; Incarnation; Islam and Christianity; comparative study